CRP/Lymphocyte Ratio and CRP/Albumin Ratio for Prognosis of Hyperglycemia in Patients Tuberculosis with Diabetes Mellitus - Sitanggang, Fardiah Tilawati; Sakdiah, Siti; Putra, Egy Sunanda (Jurnal Kesehatan Manarang, 2024)
The issue is complicated by the rise in Diabetes Mellitus (DM) cases, a known risk factor for pulmonary TB, with 15% of pulmonary TB patients having a history of DM. DM and chronic hyperglycemia impair immune function, leading to long-term inflammation and worsening TB prognosis. Diagnostic methods include blood culture, AFB examination, chest X-ray, and genotyping, but more accessible tests are needed. Inflammatory markers, particularly lymphocytes, play a crucial role in TB prognosis with DM. Lymphopenia indicates chronic inflammation and a shift to memory lymphocytes. CRP, an inflammatory marker, indicates chronic inflammation, and hypoalbuminemia in DM due to kidney damage further complicates TB prognosis. The ratios of CRP to lymphocytes (CLR) and CRP to albumin (CAR) are gaining attention to better illustrate TB prognosis with DM. This cross-sectional study analyzed CLR and CAR as prognostic indicators in 30 pulmonary TB patients with DM in Jambi City from May to June 2024. CRP was tested at Prodia Jambi Laboratory, while Albumin, Lymphocytes, and blood glucose levels were tested at Labkesda of Jambi Province. The results show a Comparison with each parameter based on treatment status. Both parameters show slightly higher average values in intensive (< 2 months), with an average of 5.55 for CLR and 1.82 for CAR, and there is a significant difference in CLR between intensive and follow-up treatment statuses, and ROC curve shows that CLR parameters have indicated high sensitivity and low false positive rate with AUC 0,692. A significant relationship is found between CLR and blood glucose levels with a p-value of 0.024 and an r-value of 0.411, indicating a moderately strong relationship where an increase in CRP-Lymphocyte ratio corresponds to an increase in blood glucose levels than each parameter.